Investment and Financial Performance: The Moderating Role of Social Capital Investment - Linh, Nguyen Ngoc Khanh; Ha, Nguyen Thu; Thao, Do Phuong (Theoretical and Practical Research in Economic Fields; Vol 17 No 2 (2026): TPREF Volume XVII Issue 2(38) June 2026, 2026)
This study examines the relationship between corporate investment and financial performance among listed construction firms in Vietnam, with a particular attention to the moderating role of sector-level social capital investment. Using a panel data for 93 listed construction companies over the period 2011-2023, combined with national data on social capital investment in the construction sector, the study applies generalized least squares (GLS) estimation to assess both market-based and accounting-based performance outcomes. The results indicate that firm-level investment is positively associated with Tobin’s Q and return on assets, with stronger effects observed for larger firms, reflecting their superior access to resources and capacity to absorb investment risks. However, higher levels of sectoral social capital investment significantly weaken this positive relationship. This negative moderation effect is consistent with the crowding-out mechanism, whereby intensified sector-wide investment heightens competition for scarce inputs, increases production costs, and reduces the marginal returns to firm-specific investment. By integrating firm-level behavior with sectoral investment dynamics, the study contributes to the literature on investment efficiency in capital-intensive industries and emerging markets. The findings also offer policy-relevant insights, emphasizing the importance of coordinating public and private investment strategies to avoid resource congestion and enhance long-term firm performance.